Embracing Watershed Politics - Blomquist, William (University Press of Colorado, 2008)
"A great book for anyone involved in watershed management issues or political science."-Tom Cech, author of Principles of Colorado Water Law for Non-Lawyers (UPC) and Water ResourcesAs Americans try to better manage and protect the natural resources of our watersheds, is politics getting in the way? Why does watershed management end up being so political? In Embracing Watershed Politics, political scientists Edella Schlager and William Blomquist provide timely illustrations and thought-provoking explanations of why political considerations are essential, unavoidable, and in some ways even desirable elements of decision making about water and watersheds. With decades of combined study of water management in the United States, they focus on the many contending interests and communities found in America's watersheds, the fundamental dimensions of decision making, and the impacts of science, complexity, and uncertainty on watershed management. Enriched by case studies of the organizations and decision making processes in several major U.S. watersheds (the Delaware River Basin, San Gabriel River, Platte River, and the Columbia River Basin), Embracing Watershed Politics presents a reasoned explanation of why there are so few watershed-scale integrated management agencies and how the more diverse multi-organizational arrangements found in the vast majorities of watersheds work. Although the presence of multiple organizations representing a multitude of communities of interest complicates watershed management, these institutional arrangements can - under certain conditions - suit the complexity and uncertainty associated with watershed management in the twenty-first century.